Life satisfaction and motives undertaking of physical activity by women aged 50-55 engaged in the fitness club - Ewa Puszczałowska-Lizis; Sylwia Musiał; Klaudia Lis; Katarzyna Pociask; Katarzyna Placek (University of Applied Sciences in Tarnow, Poland, 2017)
Aim of the study: Regular physical activity is one of the ways to prevent the negative effects of civilization and age-related involutiory changes. Recreational, referred to as an healthy lifestyle, in which physical activity is an integral element, is increasingly popular and desirable value for the modern society. The aim of this study was evaluation of life satisfaction and analysis motives of taking physical activity by fitness center clients aged 50-55. Material and methods: The study involving the method of diagnostic survey included 60 women aged 20-30, including 30 physically active, taking part in the classes offered by FIT HOUSE fitness club in Rzeszow (I group) and 30 who did not regularly participate in any physical exercises (II group). The collected research results were analyzed with the use of a non-parametric test of independence Chi-square (χ2 ) and Mann-Whitney U test. Results: Women working out in fitness club have more often declared their life satisfaction (p<0,001), satisfaction with own appearance (p<0,001) and relationships (p=0,034). We found that 70% of respondents from the first group were taking part in physical exercises due to a desire of improve the physical ability and 63% of group, in order to improve their silhouette. Conclusions: Participation in fitness clasess determines the degree of life satisfaction, apperance and social contacts of women aged 50-55. The main motive of physical effort in the fitness club is desire to improve physical efficiency and slim silhouette.